Iocn 2018 2018
DOI: 10.3390/iocn_2018-1-05500
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vinyltriethoxysilane and Maleic Anhydride Grafted Polypropylenes on the Morphological, Thermal, Rheological, and Mechanical Properties of Polypropylene/Clay Nanocomposites

Abstract: The morphology and properties of polypropylene (PP)/organoclay nanocomposites prepared by melt processing were investigated with a special interest on the different effects of the use of different grafted PP as compatibilizers, i.e., maleic anhydride or silane-grafted species, PP-g-MA or PP-g-Si. When either PP-g-MA or PP-g-Si was added, better improvement of properties was achieved. The addition of PP-g-Si was found to increase the crystallization temperature upon the clay addition in comparison to PP-g-MA. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In addition, PP possesses significant chemical resistance in polar solvents, while it is dissolved in nonpolar solvents at high temperatures. The solid semi-crystalline regions in the PP structure melt at melting points around 130 to 170 • C depending on the degree of crystallinity [16]. The degree of crystallinity of the PP strongly affects the mechanical properties, where a higher crystallinity leads to greater stiffness, yield stress, and flexural strength [15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PP possesses significant chemical resistance in polar solvents, while it is dissolved in nonpolar solvents at high temperatures. The solid semi-crystalline regions in the PP structure melt at melting points around 130 to 170 • C depending on the degree of crystallinity [16]. The degree of crystallinity of the PP strongly affects the mechanical properties, where a higher crystallinity leads to greater stiffness, yield stress, and flexural strength [15].…”
Section: Introductionmentioning
confidence: 99%
“…The thermal degradation of starch samples with MAPP started at ∼249°C and terminated at 327°C, which suggested that MAPP presence delayed starch decomposition with the peak at 473°C related to MAPP degradation. [ 51 ]…”
Section: Resultsmentioning
confidence: 99%
“…The thermal degradation of starch samples with MAPP started at $249 C and terminated at 327 C, which suggested that MAPP presence delayed starch decomposition with the peak at 473 C related to MAPP degradation. [51] DSC analysis was employed to determine the values of the overall enthalpy of the endothermic starch decomposition process (ΔH dec ) that will suggest the thermal stability of samples. [52] The thermal stability of S-ESO was somewhat decreased, which could be attributed to the presence of thermally unstable unsaturated structure and ester groups.…”
Section: Ma MC the Viscosity (ƞ) And Wetting Anglementioning
confidence: 99%